Is Declaring a Climate Emergency Enough to Stop Global Warming? Learning From the COVID-19 Pandemic - Mazon, Jordi; Pino, David; Vinyoles, Mireia (Frontiers in Climate, 2022)
One of the most important challenges our global civilization faces in the coming years is to achieve the Paris Agreement's goals of preventing the planet's temperature from exceeding the pre-industrial values of 2°C and limiting it, at most, to 1.5°C. Awareness of this problem has led to the creation of many national and international organizations in recent decades, with many thematic conferences being held and new policies to reduce greenhouse gas emissions—so far without attaining the necessary success. Among the political measures taken in recent years is the climate emergency declaration issued by many government institutions, highlighting the serious and urgent problem of climate change and the imperative need to find a solution. The COVID-19 pandemic, has led to reductions in CO2 emissions due to the substantial decreases in economic activity incurred by several countries imposing non-pharmaceutical interventions. Thus, the current practice of declaring a climate emergency must be fortified by making it a legal tool in order to reduce CO2 emissions and reach the objectives set by the Paris Agreement. Yet, what should this climate emergency declaration look like? In considering these current COVID-19-induced reductions in CO2 emissions, we hereby propose a political plan for stopping emissions to try to achieve the objectives of the Paris Agreement and at least some of the UN's 2030 Sustainable Development Goals. The article also proposes how to define the global climate alarm declaration to serve as an international legal tool for reducing CO2 and transitioning to a world free of these massive emissions. By analyzing the reduction of the emissions in different scenarios based on the COVID-19 pandemic, the article shows that the needed reduction of emissions proposed by the EU in 2030 cannot be reached in any of the scenarios limiting the CO2 emissions.